Genetics of obesity: an overview of current approaches and advancement - Asadul Mazid Helali, Farhana Matin Iti, Salwani Ismail, Mainul Haque (Journal of Applied Pharmaceutical Science, 2013)
Elucidation of obesity susceptibility genes through genome wide approaches as well as candidate gene approaches provides great promise in ultimately determining the genetic underpinnings of obesity. The complex nature of human obesity stems from the multiple interaction of several genes that control the physiology of food intake, energy expenditure, development of the body, and behavioural patterns towards food intake, and the environment. According to twin, adoptees and family studies, genetic factors account for 40-70% of the variability observed in human adiposity. Twin studies supported that the heritability of adiposity is higher than other quantitative traits. The heritability of obesity traits has been further evidenced by identification of quantitative trait loci (QTL) and genes through methods such as genome-wide scans (studies conducted on unrelated obese individuals), linkage analyses (conducted in families), and association studies (investigating the correlation between obesity and polymorphisms). The number of contributing genes, however, is still unknown. Although research on the genetic basis of obesity has advanced, the mechanisms underlying the condition are still complex due to its heterogeneity even within families.
Keywords: Obesity,Monogenic obesity,polygenic obesity,Quantitative trait loci (QTL),Leptin,Leptin receptor Gene (LEPR).